ANALYSIS OF THE EFFECT OF TAXATION KNOWLEDGE, TAXPAYER AWARENESS, TAXATION SOCIALIZATION, TAX SANCTIONS, AND E-FILLING ON TAXPAYER COMPLIANCE (Empirical Study at the Primary Tax Office in Jepara Regency, Central Java) - Adi, Suyatmin Waskito; Sanyika, Atantya Wahyu; Purbasari, Heppy (Universitas Muhammadiyah Surakarta, 2022)
The purpose of this study was to determine whether tax knowledge, taxpayer awareness, tax socialization, and e-filling affect taxpayer compliance. This research is a quantitative research that uses primary data by distributing questionnaires to every taxpayer in the KPP Pratama Jepara area. The population used in this study were all taxpayers at KPP Pratama Jepara. The sample collection method is by Convenience sampling in accordance with predetermined criteria. The sample of this study amounted to 100 taxpayers. The analysis technique used in this study is multiple linear regression analysis which is processed using the Statistical Package for Social Science (SPSS) program. The results showed that the variable knowledge of taxation and tax socialization had no effect on taxpayer compliance. While the variables of taxpayer awareness, tax sanctions, and e-filling have an effect on taxpayer compliance.